Neuronal inclusions resembling Negri bodies in the thalamus of a red kangaroo (Macropus rufus). Issue 5 (8th February 2021) - Manning, LK; Srivastava, M; Bingham, J; Curran, GC; Westermann, T; Cook, RW
Abstract : Eosinophilic intracytoplasmic neuronal inclusions resembling Negri bodies, but not associated with lyssaviral infection, were detected in the ventrolateral thalamus of a young‐adult, male red kangaroo ( Macropus rufus ). Similar neuronal inclusions, also with a regional distribution in the brain, have been reported as an incidental, possibly age‐related finding in other animal species.